Penerapan Pembukuan Digital Melalui Aplikasi Buku Warung Pada Pelaku UMKM - Tsalis Muhammad Abror (Ikatan Da'i Indonesia, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a very important role for a country, because MSMEs are influential in various economic activities. With the increasing involvement of labor in MSMEs it will help reduce the number of unemployed in this country. The main problem for MSMEs to date is regarding financial management. Financial management is the key to the success of MSMEsor even failure. The purpose of this devotion was to determine the knowledge of MSME actors regarding bookkeeping and the application of digital bookkeeping through the Buku Warung application in MSMEs. Some of the methods applied include observation, interviews, and conducting literature studies on the importance of recording financial management at the Kantin Adhyaksa and Warung Bang Jago. The implementation was carried out from May 15 to 30, 2025 in Baru Village, Baolan District, Tolitoli Regency, Central Sulawesi. The results of the application of the Buku Warung Application can help bookkeeping financial statements of MSMEs efficiently and make it possible to see business profits accurately compared to the use of manual methods. In addition, the utilization of an android-based financial information system allows users and business owners to report finances in a simple and sustainable manner, as well as increasing users understanding of simple bookkeeping and financial reporting using the Buku Warung application and encouraging user interest in implementing bookkeeping with the Buku Warung application. This service is very useful for the owners of the Kantin Adhyaksa and Warung Bang Jago business because they can utilize bookkeeping using the Buku Warung Application to record their financial statements more easily.